Le corps sans limites ou l’acéphalité : le personnage d’Acéphale, secret et équivoque, dans les oeuvres des artistes autour du Collège de Sociologie - Morando, Camille (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2006)
Acephala inflict upon the body image the sacrificial amputation of the face and the disturbing presence of a headless figure. The character Acéphale, imagined by Georges Bataille and André Masson in 1936 in Spain and personified by this headless and vigorous creature, describes the universe of confusion and savagery that surrounds them. Acéphale, the emblem of the review established by Bataille, matches up with the Collège de Sociologie's queries from 1937 to 1939, as well as with the rites of a secret society. The artists linked to the Collège de Sociologie, André Masson, Taro Okamato, and Isabelle Waldberg, question the portrayal of a headless human body. Exhibiting an acéphale enables them to question political, sexual, and social identity and to doubt the image's status and traditional iconography. These artists and writers reveal the collapse of the figuration, wishing to show the ambiguous and “headless” part of art in order to celebrate desire, the myth of absence, and the baring of the human body.